2016
DOI: 10.1186/s12968-016-0300-z
|View full text |Cite
|
Sign up to set email alerts
|

Objective criteria for septal fibrosis in non-ischemic dilated cardiomyopathy: validation for the prediction of future cardiovascular events

Abstract: BackgroundExpert subjective reporting of mid-wall septal fibrosis on late gadolinium enhancement (LGE) images has been shown to predict major cardiovascular outcomes in patients with non-ischemic dilated cardiomyopathy (NIDCM). This study aims to establish objective criteria for non-experts to report clinically relevant septal fibrosis and compare its performance by such readers versus experts for the prediction of cardiovascular events.MethodsLGE cardiovascular magnetic resonance (CMR) was performed in 118 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…It has been shown that even a small amount of LGE has prognostic implications in cardiomyopathies [ 31 34 ]. In case of inflammatory heart disease missed small subepicardial LGE may even impact diagnosis [ 35 ], as Lake Louise criteria define myocarditis as two out of three parameters, LGE being one of them [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that even a small amount of LGE has prognostic implications in cardiomyopathies [ 31 34 ]. In case of inflammatory heart disease missed small subepicardial LGE may even impact diagnosis [ 35 ], as Lake Louise criteria define myocarditis as two out of three parameters, LGE being one of them [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, late gadolinium enhancement, an independent supplementary negative prognostic sign, was found in 75% of patients in the overlapping phenotypes group [ 33 ]. The most common morphotype of LGE was linear, followed by focal, and the least common was the diffuse type; the latter particularly points toward increased risk of long-term adverse cardiovascular events [ 34 ]. The reason for such a distribution could be the greater prevalence of DCM and LVNC among patients with dilated left ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Expert subjective mid-wall septal fibrosis on late gadolinium enhancement (LGE) CM R has been shown to predict major adverse cardiovascular outcomes. Mikami et al [ 28 ] sought to establish objective criteria for non-experts and studied 118 consecutive patients with a non-ischemic cardiomyopathy and septal fibrosis identified by an expert reader. CMR naïve readers performed signal threshold-based LGE quantification.…”
Section: Cardiomyopathiesmentioning
confidence: 99%